Assessment of challenges facing functional basic education programme in Oyo State, Nigeria (2021)
This study aimed at identifying some of the problems militating against functional basic education programme and from the teaching staff point of view in Oyo State of Nigeria. A self-administered questionnaire containing six subsections with forty-five (45) questionnaire items were utilized for this study. The overall reliability coefficient of the instrument used is 0.79. While stratified random sampling technique was used in this study and the sample size used is 519 participants that are made up of the teaching staff of all cadres. The study found, among others that, the teaching staff are not satisfied with the condition of service due to high handedness on the parts of AOPSHON executive and LGEA office officers, that the representative of SUBEB at each LGEA Office is not fair to the teaching by way of transferring their job to AOPSHON, that the teaching staff are not satisfied with the way the AOPSHON executives are running the affairs of primary education in Oyo state, that the teaching staff in primary school do not have freedom of expression in course of discharging their duties and finally the teaching staff suggested the ways that can make basic education progresses in Oyo state. The authors insist that appropriate authority should be put in place to forestall on timely death among primary school teaching staff due to high handedness of few privilege groups of people over one another. All official assignment should be taken away from labour association (AOPSHON) to prevent unnecessary punishment and harassment from so-called union executives. School monitoring and supervision should be handled by the Education Ministry and SUBEB officers and not AOPSHON executives. The number of qualified teachers that Oyo state have are okay enough for formidable academic output from the learners but the situation the teaching staff found themselves are not palatable for the teaching staff to perform optimally. School monitoring and supervision, duty post, promotion, and transfer in each local government must be a conscious exercise of SUBEB and State Ministry of Education and not the function of teachers‟ labour union at all.